Efficacy and tolerability of metallic stent in patients with malignant prostatic obstruction secondary to prostatic cancer. Issue 3 (25th March 2021) - Choi, Se Young; Lim, Bumjin; Chi, Byung Hoon; Kim, Jung Hoon; Lee, Wonchul; Kyung, Yoon Soo; You, Dalsan; Song, Ho‐Young; Kim, Choung‐Soo
Abstract: Objective: To evaluate the efficacy and tolerability of a self‐expandable covered metallic stent in patients with malignant prostatic obstruction secondary to prostate cancer (PC). Methods: We reviewed 22 cases of insertion of self‐expandable covered metallic stents with barbs. Data were collected about PC status. Uroflowmetry variables, residual urine volume, International Prostate Symptom Score (IPSS), quality of life (QOL), and duration from stent insertion to removal were surveyed. These clinical parameters were compared before and after stent insertion. Results: The patients with PC showed a mean age of 75.5 ± 6.5 years and mean 5.1 ± 1.9 Charlson comorbidity index. The average flow rate (2.4 ± 1.9 vs 5.9 ± 2.4 mL/s, P = .005), peak flow rate (6.9 ± 6.2 vs 14.1 ± 5.5 mL/s, P = .003), flow time (54.6 ± 29.1 vs 23.6 ± 13.7 s, P = .002), residual urine volume (178.7 ± 195.5 vs 7.0 ± 7.1 mL, P = .004), IPSS (26.2 ± 8.1 vs 8.0 ± 6.5 points, P = .001), and QOL (4.7 ± 1.3 vs 2.4 ± 2.1 points, P = .030) improved between before and after stent insertion, respectively. Pain was the most common complication, but 60% of the patients were managed without any intervention. There were hematuria, urinary retention, urinary frequency, obstruction, and urinary incontinence. However, there was no urinary tract infection due to the stent. The median time to stent removal was 5.7 months. Conclusions: The stent was maintained for about 6 months with improved objective and subjective outcomes. The patients with PC, who had a poor comorbidity index and advanced PC status showed a tolerable maintenance period. Self‐expandable covered metallic stents can be used for PC patients with a short life expectancy and unsuitability for general anesthesia.